Preparation of High Porous Poly(2-ethylhexyl methacrylate-co-ethylene Glycol Dimethacrylate) Monolithic Columns for Fast Separation of Small Molecules - K. Al-Shammari1, Hessa; Aqel2, Ahmad; A. Alothman2, Zeid (Asian Journal of Chemistry, 2014)
This paper describes the fabrication of monolithic materials for use as stationary phases in capillary liquid chromatography. Four columns were synthesized in the confines of 320 μm i.d. and 200 mm long fused-silica capillaries using a single step in situ copolymerization of 2-ethylhexyl methacrylate and ethylene glycol dimethacrylate (EDMA). The polymerization procedure was optimized; ethylene glycol dimethacrylate crosslinker content showed predominant influence on the columns characteristics. Changes of the porous and hydrodynamic properties of the prepared monolithic columns were thoroughly investigated and their morphologies were characterized by examining the scanning electron microscopy images and Fourier transform infrared spectra. A decrease in the porogen to monomer ratio corresponded to smaller microglobules and a lower total porosity. The microglobules had an approximate diameter in the range of 1-2 μm. The total porosities ranged from 73 to 80 % using the retention times of uracil as an unretained marker. The resulting monoliths exhibited good permeability and mechanical stability, while swelling behaviour was observed and discussed. The efficiency and performance towards different sets of analytes were obtained; mixtures of aromatic hydrocarbons and phenolic compounds were successfully separated and evaluated. Fast separations were achieved in less than 5 min for the model compounds.